Tooth # 19 Full Cast Crown Preparation Chamfer - Meir Kozlovsky; Kumar Shanmugam; William Skiba; Peter Furnari (Association of American Medical Colleges, 2011)
Abstract This resource contains a 20-minute long, fully-narrated instructional video depicting the stepwise procedure for the preparation of tooth #19, a mandibular left first molar, for a full crown cast restoration using a chamfer-type finishing line. The procedure is performed on a mannequin mandible. The presentation goes from the unprepared tooth to the completed preparation with access to the facial, mesial, distal, occlusal, and lingual aspects of the tooth by means of chapter markers. The audio-video presentation of the preparation of a mandibular tooth to be restored with a full cast crown serves as a guide for the understanding and implementation of the procedure. The visuals allow for enhanced and enlarged unobstructed close-up views. The narration explains precisely why and how the procedure is performed.